Harmony as a Gravitational Functional and Aesthetic Center of the System of Poetic Text Characteristics - Y. V. Kazarin (Научный диалог)
The study was carried out as part of the poetological direction of modern linguistics of text and textual science. The harmony in the status of a new feature of the text (both artistic and poetic) is considered. Poetic harmony is understood as an aesthetic, functional-denotative, semantic, notional, formal-substantive and systemic-structural center of a poetic text. The regular conceptual relationships of poetic harmony with other textual features are characterized. Such features of the text as systematicity, structurality, functionality and the rest (categorical, differential and additional) are interpreted by the author of the article as the result of the action of the basic properties of harmony: firm order, proportionality, harmony, perfection, beauty, truth, goodness, desire for the Absolute, etc. It is asserted that when correlating the category of “poetic harmony” with well-known textual features, conceptual oppositions of an expanded type are built up, when various aspects of these concepts and corresponding notations appear in the relations of intersection. In addition to the formal-substantive and functional paradigmatic aspects, ethical-aesthetic, perfectionist, energetic and other aspects of these phenomena are also taken into account. It is proved that the general feature of the poetic text “self-organization” enters with the concept of “harmony” into the relationship of identity with elements of partivism. It is concluded that poetic harmony in the system of signs of the poetic text turns out to be the organizing, systematizing “gravitational center”.